Plasma prolactin among superovulated prepuberal buffaloes (Bubalus bubalis) - Singh, C; Madan, M L (The Indian Journal of Animal Sciences, 2012)
Eight Murrah buffalo heifers of 12 months of age wen: used to study the effect of synchronizing and superovulatory treatment of PGF2a and PMSG combination on prolactin release. The GnRH (FertagyI) 200 µg was injected (i/v) in 4 heifers (experimental group) while saline (2 ml) was injected (i/v) in the remaining 4 heifers (control group) at induced estrus. Blood samples were collected through jugular catheter for prolactin estimation. The plasma prolactin level before first PGF2a administration (basal value) was similar in both experimental (123.30 ± 17.41 ng/ml) and control ( 129.19 ± 7.55 ng/ml) groups. The level was elevated by 24 to 48 hr of PMSG injection and maintained at higher value on subsequent days during follicular phase among both experimental (195.16 ± 8.28 to 251.60 ± 33.73 ng/ml) and control (217.52 ± 36.58 to 225.51 ± 8.27 ng/ml) groups, The difference between plasma prolactin level recorded during oestrus among experimental ( 184.77 ± 6.97 to 260.81 ± 22.73 ng/ml) and control (218.68 + 20.33 to 250.93 ± 34.70 ng/ml) group heifers was not signiticant (P>0.05). However, a significant (P < 0.01) elevation of prolactin was maintained throughout the follicular phase after PMSG administration. GnRH injection at induced estrus did not have any influence per se at prolactin level.